Wettbewerb Dom - Römerberg in Frankfurt/M. - Rumpf, Peter; Klingeren, Frank von (My University, 1980)
1.Preis: Bangert, Jansen, Scholz, Schultes, Berlin; 2.Preis: Albrecht, Jordan, Mueller, Bernhof, Frankfurt; 3.Preis: Hadamczik, Hannover; 6.Preis: Moore, Los Angeles. of
Keywords: Stadterneuerung; Wettbewerb; Ensemble; Platzgestaltung; Schirm; Kommunikation